NUMERICAL SIMULATION OF ELECTRIC CHARACTERISTICS OF DEEP SUBMICRON SILICON-ON-INSULATOR MOS TRANSISTOR - A. V. Borzdov; V. M. Borzdov; N. N. Dorozhkin (Приборы и методы измерений)
Today submicron silicon-on-insulator (SOI) MOSFET structures are widely used in different electronic components and also can be used as sensing elements in some applications. The development of devices based on the structures with specified characteristics is impossible without computer simulation of their electric properties. The latter is not a trivial task since many complicated physical processes and effects must be taken into account. In current study ensemble Monte Carlo simulation of electron and hole transport in deep submicron n-channel SOI MOSFET with 100 nm channel length is performed. The aim of the study is investigation of the influence of interband impact ionization process on the device characteristics and determination of the transistor operation modes when impact ionization process starts to make an appreciable influence on the device functioning. Determination of the modes is very important for adequate and accurate modeling of different devices on the basis of SOI MOSFET structures. Main focus thereby is maid on the comparison of the use of two models of impact ionization process treatment with respect to their influence on the transistor current-voltage characteristics. The first model is based on the frequently used Keldysh approach and the other one utilizes the results obtained via numerical calculations of silicon band structure. It is shown that the use of Keldysh impact ionization model leads to much faster growth of the drain current and provides earlier avalanche breakdown for the SOI MOSFET. It is concluded that the choice between the two considered impact ionization models may be critical for simulation of the device electric characteristics.